Design and Fabrication of a Quail Egg Shell Peeler with Automatic Counter System: Improving Productivity in Small-Scale Egg Processing - Maulana, Ridwan; Rifandi, Safriudin; Subur, Joko (J-Eltrik, 2024)
Quail eggs are one type of food that is widely consumed by the Indonesian people. The design of an automatic quail egg peeler aims to help batagor traders who use quail eggs as one of the main ingredients. This tool is designed to increase the efficiency of the quail egg peeling process which has been done manually, is time-consuming, and requires a lot of energy, especially for elderly traders. This peeler is equipped with a counter technique that can automatically count the number of eggs that have been peeled, making it easier for traders to monitor daily production. The peeling mechanism involves breaking the shell and peeling the egg skin using a rotating roller. The sensor on this tool detects each egg that is successfully peeled and adds the number to the digital counter. The test results show that this tool can peel quail eggs with a high success rate and in a shorter time than the manual method. This automatic quail egg peeler is expected to be an efficient and practical solution for batagor traders, especially the elderly, to increase productivity and reduce workload.